Hidden Burden of Cystic Echinococcosis in Arequipa, Peru: An Unrecognized Population at Risk - Ricardo Castillo-Neyra; Wilfredo Victor Gutiérrez Zarate; María Paula Requena-Herrera; Lizzie Ortiz-Cam; Guillermo Porras; Jesus Marcelo Manturano Lopez; Jose Fernando Macedo Milla; Jorge L. Cañari-Casaño; Javier A. Bustos (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Peru carries the highest burden of cystic echinococcosis (CE) in South America, yet major geographic gaps persist in understanding the distribution and intensity of the disease. The Arequipa region in southern Peru has historically been considered nonendemic, with no previous systematic clinical characterization of CE, despite increasing reports. Clinical records of 129 of 177 CE surgical cases treated between December 2011 and November 2013 at a government-funded CE surgical unit at a major referral hospital were analyzed. This represents the first structured clinical assessment of CE in Arequipa. Sociodemographic, epidemiological, and clinical data were extracted, and cases were mapped at a provincial level. Statistical analysis was conducted using appropriate nonparametric and exact tests. Half of Arequipa’s provinces of origin (4/8) had case rates of 7.8 to 20 per 100,000, substantially exceeding the national average. Notably, 40.3% of CE surgical cases were autochthonous to Arequipa, suggesting local transmission years before treatment, consistent with CE’s prolonged incubation period. Patients had a median age of 26 years (interquartile range: 16–45 years), 55% were male, and 69% were students (35%), farmers (18%), or homemakers (16%). Pulmonary involvement predominated, accounting for 70% of cases. Comparison of patient- and cyst-level characteristics between Arequipa and established CE-endemic regions revealed no significant differences. These findings reveal a substantial and previously underrecognized clinical CE burden in Arequipa, providing foundational baseline evidence for a region newly recognized as endemic. Evidence of local transmission underscores the urgent need for sustained political support, specialized surgical units, and systematic surveillance to strengthen CE control in southern Peru.